O ensino de filosofia da educação nos cursos de pedagogia na Universidade Federal de Mato Grosso do Sul - Silva, José Carlos da (Universidade Federal de São Carlos, 2007)
The teaching of philosophy of the education in the courses of pedagogy in the Federal University of Mato Grosso do Sul, in the period from 1999 to 2003, is the object of inquiry of this work, and it was structuralized in two parts. In the first , we made an approach to this object of study, showing the historical root of the relation between philosophy and education, the ways of the teaching of philosophy in Brazil and the relations between philosophy, politics and education in the thought of Antonio Gramsci. In the second part, we carry through the analysis of the study object. On the basis of the found concrete data we describe how professors teach philosophy of education. After knowing the professors academic profiles, the documents found and the testimonials collected through interviews with professors and pupils were appreciated and analyzed. In this manner, we exceed the common sense, revealed the estimates and theoreticalmethodologicals referentials that have based this practice of teaching. The research disclosed that, although inserted in an economically, semi-industrialized farming State, at a moment of world Wide hegemony by the globalized neoliberal capitalism, the professors, in its majority, have acted influenced, direct or indirectly, by the marxist theoretical-methodological referential, especially by the historicism of Antonio Gramsci. The research has put in evidence the motivations that have taken the professors to adopt this referential, its advances and contradictions existing in the pedagogical practice, its mistakes, its limits that can be surpassed so that this academic praxis my be more coherent with the adopted referential and the goals assumed.
Keywords: Educação - filosofia; Filosofia marxista; Gramsci, Antônio, 1891-1937; Ensino; Teaching; Fhilosophy; Education; Marxism; Antonio Gramsci; CIENCIAS HUMANAS::EDUCACAO